STRUKTUR DAN FUNGSI LAGU BANJAR KARYA H. ANANG ARDIANSYAH - Kamariah Kamariah; Ngalimun Ngalimun (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The purpose of this research is to study the structure and function of the Banjar regionalsongs. Besides carrying out the mission of revitalizing Banjar culture which has begun tobecome extinct along with the times. This research uses descriptive method so the results of thisstudy are the results of research on Banjar by H. Anang Ardiansyah. For accurate andunderstandable analysis data, this study uses an objective method, which is based on the literarywork itself. This method is expected to reveal the form and function contained in the Banjarsong.The structure of the Banjar song by H. Anang Ardiansyah can be changed into two,namely the repetition of parts and repetition with changes. Bait full repeat loop. Repetition withthe changes requested in the repetition of feedback in the first few lines is the same, but inseveral lines after the change in feedback. This research also succeeded in formulating fourfunctions of the Banjar song, namely the function of educating or helping, entertaining,criticizing, and expressing feelings.